Artificial Intelligence Capabilities in Digital Financial Service Systems: The Role of Internal Control Effectiveness as an Information Governance Mechanism in Enhancing Information Quality in Islamic Banks - Almatarneh, Zeyad; Alawneh, Nabeela Fares; AL-Jarrah, Mahmoud Mefleh; Jarah, Baker Akram Falah; Abuirrmilah, Bassam (International Review of Management and Marketing, 2026)
This study examines the role of Artificial Intelligence capabilities within digital financial service systems in enhancing information quality through internal control effectiveness as an information governance mechanism in Islamic Banks. This study utilizes the Resource-Based View, Dynamic Capability Theory, and Agency Theory to formulate a technological capability, governance, and information outcome model. This study uses a quantitative approach through the use of survey data of 265 Islamic bank employees and structurally analyzes that data using the Structural Equation Model. The model outcome showed AI had a positive outcome on both the effects of internal controls and the effects of information quality. The study also showed that the greatest impact of AI was on the effects of internal control, suggesting that the role of AI is critical to enhancing the governance role of internal control. The study results also showed that the internal control effects improved the quality of the information and that the control effects partially mediated the relationship between AI and the quality of the information. The study also showed AI had both a direct and governance-effect causal relationship with the quality of information. The study also showed that the role of AI governance is through the control systems more than other technologies' roles. The study is a contribution to the literature, as the AI Governance role is at the systems control level and that for the digital systems of the financial services industry to acquire systems to high levels of information quality.